Nucleotide Excision Repair and Transcription-coupled DNA Repair Abrogate the Impact of DNA Damage on Transcription - Nadkarni, Aditi (J Biol Chem, 2016)
DNA adducts derived from carcinogenic polycyclic aromatic hydrocarbons like benzo[a]pyrene (B[a]P) and benzo[c]phenanthrene (B[c]Ph) impede replication and transcription, resulting in aberrant cell division and gene expression. Global nucleotide excision repair (NER) and transcription-coupled DNA repair (TCR) are among the DNA repair pathways that evolved to maintain genome integrity by removing DNA damage. The interplay between global NER and TCR in repairing the polycyclic aromatic hydrocarbon-derived DNA adducts (+)-trans-anti-B[a]P-N(6)-dA, which is subject to NER and blocks transcription in vitro, and (+)-trans-anti-B[c]Ph-N(6)-dA, which is a poor substrate for NER but also blocks transcription in vitro, was tested. The results show that both adducts inhibit transcription in human cells that lack both NER and TCR. The (+)-trans-anti-B[a]P-N(6)-dA lesion exhibited no detectable effect on transcription in cells proficient in NER but lacking TCR, indicating that NER can remove the lesion in the absence of TCR, which is consistent with in vitro data. In primary human cells lacking NER, (+)-trans-anti-B[a]P-N(6)-dA exhibited a deleterious effect on transcription that was less severe than in cells lacking both pathways, suggesting that TCR can repair the adduct but not as effectively as global NER. In contrast, (+)-trans-anti-B[c]Ph-N(6)-dA dramatically reduces transcript production in cells proficient in global NER but lacking TCR, indicating that TCR is necessary for the removal of this adduct, which is consistent with in vitro data showing that it is a poor substrate for NER. Hence, both global NER and TCR enhance the recovery of gene expression following DNA damage, and TCR plays an important role in removing DNA damage that is refractory to NER.